THE RELATIONSHIP BETWEEN OCCUPATIONAL HEALTH (K3) AND MOTIVATION WITH EMPLOYEE PERFORMANCE AT PT. SARANA BANDAR NASIONAL SURABAYA - Afif Subarkah; Hermin Tridayanti (NAROTAMA UNIVERSITY, Indonesia, 2018)
With the various demands regarding occupational health and safety issues, companies must be able to fulfill their responsibilities in protecting employees by carrying out occupational health and safety programs. It is only natural that the workforce also plays an active role and takes responsibility for the implementation of programs for the maintenance and improvement of welfare for the realization of good protection for workers and their families. So, not only the company is responsible for this problem, but employees must also take an active role in this to achieve common welfare. Based on the description above, the purpose of this study aims to determine the relationship between K3 and Motivation with Employee Performance at PT. Surabaya National Airport Facility. The population used in this study are employees of PT. Sarana Bandar Nasional Surabaya with samples taken were 40 respondents. The research model uses Spearman rank correlation to test the significance of the hypothesis. Based on data analysis and discussion of the research results that have been stated, it can be concluded that the following questions are answered: Occupational safety and health have a moderate relationship with employee performance. Motivation has a strong relationship with employee performance.